2009
DOI: 10.1111/j.1540-8159.2009.02403.x
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Mechanical Assist Devices and Cardiac Device Interactions: An Observational Case Series

Abstract: LVADs have a definite impact on cardiac devices in respect with alteration of lead parameters, ventricular tachyarrhythmias, and electromagnetic interference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 19 publications
3
43
1
Order By: Relevance
“…In addition, ventricular arrhythmias can cause lower LVAD flows, predispose patients to development of LV thrombus formation, and result in hemodynamic compromise in some patients. 7,10 In this study, we found that almost 25% of patients received an appropriate ICD shock for a ventricular arrhythmia, which provides some evidence that the use of ICDs in patients with LVADs may be justified. Potential predictors for receiving ICD shocks that were found in this study included male gender, non-Caucasian race and LVAD placement as destination therapy.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, ventricular arrhythmias can cause lower LVAD flows, predispose patients to development of LV thrombus formation, and result in hemodynamic compromise in some patients. 7,10 In this study, we found that almost 25% of patients received an appropriate ICD shock for a ventricular arrhythmia, which provides some evidence that the use of ICDs in patients with LVADs may be justified. Potential predictors for receiving ICD shocks that were found in this study included male gender, non-Caucasian race and LVAD placement as destination therapy.…”
Section: Discussionmentioning
confidence: 85%
“…Two studies reported that after LVAD implant, right ventricular ICD leads have a decrease in R-wave amplitude, a decrease in impedance, and an increase in capture threshold even among leads that with previous, chronically stable characteristics. 38,39 This can result in various ICD problems, including failure to sense VAs, failure to capture, and inappropriate pacing caused by undersensing. We have also observed interference that likely resulted from interaction of a very apically placed chronic right ventricular defibrillator lead with the inflow cannula apparatus (Figure 3).…”
Section: Icd Therapymentioning
confidence: 99%
“…R-wave amplitude often decreases after VAD implant, possibly because of left ventricular core removal for cannula insertion and remodeling. 63,64 Thus, the ICD operates at a more sensitive setting, increasing the risk of oversensing all extracardiac signals. Because the power line or motor is often in close proximity to the sensing bipole near the RV apex, VAD EMI often has greater amplitude on the sensing channel [65][66][67] than the shock channel.…”
Section: Medical Sourcesmentioning
confidence: 99%